The influence of mudarabah & musharakah microequity financing principles on poor women entrepreneurs in Selangor / Reazul Islam - Reazul , Islam (2018)
So far, Mudarabah and musharakah (M&M) financial instruments have not been offered by any microfinance institution in Malaysia. This study aims to explore whether these instruments can be introduced to the entrepreneurial poor women in Selangor. For this purpose, the levels of the clients’ product-knowledge, religiosity, and entrepreneurship were assessed while determining their willingness of accepting the Shariah principles of M&M. This study also statistically scrutinizes the influence of the Shariah principles of M&M financing on the entrepreneurship of the poor clients. It further examines the impacts of clients’ knowledge of M&M, religiosity and specific socio-demographic characteristics (education, income, savings, and business experiences). Quantitative and qualitative research methods were adopted to achieve the aim. A survey was carried out in Selangor by using a self-generated structured questionnaire by the end of 2014 and early 2015. A total of 330 (n) questionnaires were retrieved from the equal number of disadvantaged entrepreneurial Muslim women who were the members of Amanah Ikhtiar Malaysia (AIM). The data were analysed by means of exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM). To enhance the validity and reliability of the findings of the quantitative study, the methodological triangulation technique was employed. Two academic scholars and one industrial expert were interviewed with an open-ended questionnaire. Findings of the quantitative study suggest that poor women entrepreneurs in Selangor possess the basic knowledge of M&M financing. They lead an intrinsic religious life performing ‘general worshipping’. Their entrepreneurial skills lay at the moderate level that can be categorised as aspiring entrepreneurship. They are willing to accept those Shariah principles that are commonly used in the general partnership business. The results of the inferential statistical suggest that Shariah principles of M&M have a partial positive impact on the entrepreneurship. The mediating effect of religiosity is higher than that of knowledge. Besides, the variations of mudaribs’ academic-qualification, income, savings and business experience have trivial moderating effects. But the output of the qualitative study is somewhat different. All the experts were univocal on knowledge, religiosity, and entrepreneurship as the selection criteria of the clients. They opined that clients could perform better under the business rules of Shariah. According to their views, academic qualification and business experience are necessary to enhance clients’ business performance. They affirmatively stated that income and savings have important roles in shifting the mudarib from mudarabah contract to musharakah contract. They further asserted that the inclusion of musharakah mutanaqisah in microfinance would be an appropriate approach to alleviate poverty in a sustainable manner. Hence, the overall findings of this study suggest that mudarabah and musharakah (M&M) financial instruments can be offered to the disadvantaged Muslim women in Selangor. But the further improvement of their knowledge, religiosity and entrepreneurship might bring greater viability to these financing. The findings of this study would be helpful to the Malaysian microfinance institutions to introduce M&M based micro-equity finance. Since this study was confined to Selangor it might not represent the whole scenario of Malaysia. Therefore, further research is needed.